Respuesta :

Answer:


Step-by-step explanation:

Simplifying

16 = -12 + -7x


Solving

16 = -12 + -7x


Solving for variable 'x'.


Move all terms containing x to the left, all other terms to the right.


Add '7x' to each side of the equation.

16 + 7x = -12 + -7x + 7x


Combine like terms: -7x + 7x = 0

16 + 7x = -12 + 0

16 + 7x = -12


Add '-16' to each side of the equation.

16 + -16 + 7x = -12 + -16


Combine like terms: 16 + -16 = 0

0 + 7x = -12 + -16

7x = -12 + -16


Combine like terms: -12 + -16 = -28

7x = -28


Divide each side by '7'.

x = -4


Simplifying

x = -4